Financial Absorption Rates in EU Objective 1 1994-99 and Some Lessons for the New Member States in 2004-2006 - Andrej Horvat (Austrian Institute of Economic Research (WIFO), 2005)
In this paper we would like to draw attention on the fact how important for the absorption of the EU funds might be each country's or region's split of its financial portfolio between EU, national and private sources of co-financing. Based on data from the Ex-Post Evaluation 1994-99, this paper provides information on financial absorption in the Objective 1 areas of Member States in the 1994-1999 period. We were interested in which financial components are "more easily" absorbed and, consequently, what lessons regarding the potential "allocation trap" for the New Member States could be drawn here? We also compared our results with the situation in the programming documents of Hungary, the Czech Republic, Slovakia, Estonia and Slovenia made respective conclusions.
Keywords: 330; EU-Strukturfonds; Subvention; EU-Mitgliedschaft